أثر سرعة الفصل في الخصومة في تحقيق الأمن القضائي في الشريعة الإسلامية - غمام عمارة, أحمد (University of Eloued جامعة الوادي, 2014)
يسلط هذا المقال الضوء على مسألة أهمية سرعة الفصل في الخصومات، ودورها في تحقيق الأمن القضائي من بيان أهمّ مرتكزات وأركان القضاء في الإسلام، والتأصيل الشرعي لمبدأ سرعة الفصل في الخصومات، وتوضيح ملامح ومظاهر سرعة الفصل في القضاء وأثرها في تحقيق الأمن القضائي. This research deals with the issue of the importance of prompt settlement of litigation, and its role in ensuring of security judicial, and that by addressing the most important basis of justice in Islam, and founding of prompt settlement of litigation, and to clarify the features and aspects of prompt settlement of litigation and their impact in the ensuring of judicial security.
مقال بمجلة البحوث والدراسات
Keywords: الخصومة- الأمن- القضاء- الحكم الشرعي- التعجيل بالحكم; litigation - security - the judiciary - Islamic ruling - expedite the issuance of judgment